APPLICATIONS OF MICROBIAL ALPHA AMYLASE IN SUGAR, BAKING, TEXTILE AND OTHER INDUSTRIES - Ali, Sikander; Mohsin, Zainab; Shamsher, Nazia; Khan, Fatima Sana (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Amylases are the most major significant enzymes which are used in industry. Amylases have many substantial applications, as nutrition, yeast and therapeutic industries. α -amylases can be gained from flowers, beasts, germs and a solitary family. For the manufacture of α -amylase, the important step is to convert the simple starch molecules into oligosaccharides. Variations in microbial α -amylases are used in altered business sectors i-e nutrition, cloth, daily and cleansing agent industries. The synthesis of α -amylase has been carried out by using immersed fermentation. The features of α -amylase involve thermo stability, pH assortment, pH firmness and Calcium-independency; which play a strategic role in the process of fermentation. . By the use of α -amylase in starch hydrolysis, applied for industrial uses, as washing and ceramic cleansing agent or as anti-staling managers in roasting. In this review article we engrossed on the industrial applications of microbial α -amylase